Global investments - Solnik, Bruno H. (Pearson, 2014)
Global Investments, the Sixth Edition of the previously titled International Investments, provides accessible coverage of international capital markets using numerous examples to illustrate the applications of concepts and theories. The new title reflects the current understanding that the distinction between domestic and international is no longer relevant and that asset management is global. This book is ideal for CFA(r) (Chartered Financial Analyst) candidates, advanced finance undergraduates, and MBA students, and it has been selected by the CFA Institute as part of the curriculum to deliver the Candidate Body of Knowledge for the CFA. The text is also widely used by professionals working in the investments area, as the level is accessible to students and portfolio managers without recent training in portfolio theory.